2018
DOI: 10.1007/s00059-018-4699-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed vs. immediate stenting in STEMI with a high thrombus burden

Abstract: DS yielded satisfactory outcomes regarding myocardial tissue reperfusion, demonstrated by the improved TIMI flow grade, TMBG, complete ST-segment resolution, and decreased MACEs without increasing major bleeding events in patients with STEMI and a high thrombus burden. DS may be preferred to IS for treating patients with this characteristic presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
3
0
3
Order By: Relevance
“…The study of Carrick et al [39] demonstrated that, in high-risk STEMI patients, deferred stenting is associated with fewer intraprocedural thrombotic events, higher TIMI flow grade and increased myocardial salvage compared with immediate stenting. Similarly, a recent meta-analysis including 744 patients demonstrated that a deferred stent implantation strategy was associated with improved TIMI flow grade, greater TIMI myocardial blush grade and decreased MACEs without increasing major bleeding events in STEMI patients with a high thrombus burden [40]. Besides, it has been suggested that use of intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT), which ascertains the predisposing mechanical factors of ST, may be a potential adjunctive therapy for EST [41,42].Thus, it seems reasonable to consider that aggressive EST cases can benefit from a deferred PCI strategy with intra-coronary imaging after optimal medical therapy.…”
Section: Discussionmentioning
confidence: 94%
“…The study of Carrick et al [39] demonstrated that, in high-risk STEMI patients, deferred stenting is associated with fewer intraprocedural thrombotic events, higher TIMI flow grade and increased myocardial salvage compared with immediate stenting. Similarly, a recent meta-analysis including 744 patients demonstrated that a deferred stent implantation strategy was associated with improved TIMI flow grade, greater TIMI myocardial blush grade and decreased MACEs without increasing major bleeding events in STEMI patients with a high thrombus burden [40]. Besides, it has been suggested that use of intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT), which ascertains the predisposing mechanical factors of ST, may be a potential adjunctive therapy for EST [41,42].Thus, it seems reasonable to consider that aggressive EST cases can benefit from a deferred PCI strategy with intra-coronary imaging after optimal medical therapy.…”
Section: Discussionmentioning
confidence: 94%
“…При этом в группе пациентов с ОСКА, где имплантация стента не выполнялась, первичные ангиографические точки по шкале TIMI и MBG были значительно лучше, чем в контрольной группе НСКА. ОШ получить лучшие показатели в группе ОСКА по сравнению с НСКА составили 3,8; (1,2-11,8) и большую частоту резолюции подъема сегмента ST на 70 и более процентов -3,7; (1,(3)(4)(5)(6)(7)(8)(9)(10)5). Важно, что результаты нашего 5-летнего наблюдения показывают относительную безопасность этой стратегии, как по частоте необходимости повторных реваскуляризаций в ИСКА, так и по частоте повторных ИМ, по частоте фатальных осложнений.…”
Section: Discussionunclassified
“…[1,5]. Помимо того, что и дилатация коронарным баллонным катетером, и имплантация стента рекомендованным давлением в сохраняющиеся тромботические массы неизбежно несут риск развития дистальной эмболизации и, как следствие, приводят к ухудшению перфузии миокарда, но и сам по себе коронарный стент в дальнейшем повышает риски развития внутрисосудистых осложнений, таких как тромбоз и рестеноз внутри стента, особенно у пациентов с массивной тромботической нагрузкой, а имплантация стента в остаточное стенотическое поражение не влияет на кардиальную смерть [4,[6][7][8][9].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…TIMI flow grading has proven a useful tool in patients with acute MI and is used routinely in clinical practice. 10,11 Because of its significant relevance to the overall outcomes, multiple investigations have focused on describing risk factors and strategies to minimize TIMI flow grades 0 to 2 following reperfusion.…”
Section: Introductionmentioning
confidence: 99%